Development of a Contextual-Based Mathematics Learning Module to Improve Mathematical Literacy of Seventh-Grade Students at State Junior High School 05 Bengkulu City - Yona Christiana; Adi Asmara; Hilyati Milla (Journal of Research in Social Science and Humanities, 2026)
This study aimed to develop a contextual-based mathematics learning module on algebra material to improve the mathematical literacy of seventh-grade students at SMP Negeri 05 Bengkulu City. The study was motivated by the low level of Indonesian students’ mathematical literacy as reported by the Organisation for Economic Co-operation and Development through the Programme for International Student Assessment (PISA) 2022, which indicates that most students are still below the minimum competency level. Preliminary observations at the research site also revealed that mathematics learning tends to focus on procedural exercises and abstract problems, with limited connection to students’ real-life contexts. This research employed a Research and Development (RD) approach using the ADDIE model, which consists of the stages of Analyze, Design, Develop, Implement, and Evaluate. The limited trial subjects involved 29 seventh-grade students and one mathematics teacher. The research instruments included expert validation sheets for material and media, practicality questionnaires for students and teachers, and a mathematical literacy test based on PISA indicators. The results indicated that the developed module met the criteria of high validity, with an average material validation score of 3.50 (very good category), media validation score of 3.025 (good category), and language validation score of 3.86 (very good category). The practicality of the module based on students’ responses obtained an average score of 3.14 (interesting category), while the teacher’s response reached 3.65 (very feasible category). The use of the module improved students’ learning mastery, reaching more than 90%, indicating that the module is valid and practical for use in mathematics learning.